2016
DOI: 10.1083/jcb.201603062
|View full text |Cite
|
Sign up to set email alerts
|

ASB7 regulates spindle dynamics and genome integrity by targeting DDA3 for proteasomal degradation

Abstract: Uematsu et al. show that ASB7 ubiquitinates DDA3, which facilitates Kif2a-mediated depolymerization of microtubules (MTs) for proteasomal degradation. The presence of MTs prevents the ASB7–DDA3 interaction, suggesting a feedback loop to appropriately regulate MT polymerization and spindle dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Accompanied by the resumption of meiosis, ASB7 protein appeared to be colocalized with chromosomes (Figure 1). Furthermore, we found that ASB7 depletion resulted in the failure of spindle assembly and chromosome congression in oocytes and aneuploidy generation (Figure 3), similar to the observations in HeLa cells (Uematsu et al, 2016). Kinetochore is a complex structure that establishes the attachment of spindle microtubules to chromosomes and is thus essential for faithful chromosome segregation (Santaguida and Musacchio, 2009).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Accompanied by the resumption of meiosis, ASB7 protein appeared to be colocalized with chromosomes (Figure 1). Furthermore, we found that ASB7 depletion resulted in the failure of spindle assembly and chromosome congression in oocytes and aneuploidy generation (Figure 3), similar to the observations in HeLa cells (Uematsu et al, 2016). Kinetochore is a complex structure that establishes the attachment of spindle microtubules to chromosomes and is thus essential for faithful chromosome segregation (Santaguida and Musacchio, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Altogether, our data support a model where ASB7, likely through the modulation of K-MT interaction, controls SAC signaling, consequently ensuring the proper assembly of meiotic apparatus in mammalian oocytes. Recently, it has been reported that the ASB7 protein regulates mitosis by targeting DDA3 (differential display and activated by p53) through proteasomal degradation (Uematsu et al, 2016). Future investigation is needed to clarify (i) whether this pathway is functional during mouse oocyte maturation and (ii) whether there are any other specific targets mediating the action of ASB7 on meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASB2 was found to interact with Cullin5 and Rbx2 to form E3 ubiquitin ligase complexes [ 18 ]. ASB7 degrades DDA3 to regulate spindle dynamics and genome integrity [ 19 ]. ASB9 targets ubiquitous mitochondrial creatine kinase (uMtCK) and regulates mitochondrial function [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of E3 ubiquitin ligases is a vital mechanism through which ER stress improves degradation of misfolded ER proteins [ 44 , 45 ]. Previously, ASB7 has been reported to play a crucial role in regulating spindle dynamics and genome integrity by controlling the expression of DDA3 [ 46 ]. However, the regulation of ASB7 gene in ER stress is not yet explored.…”
Section: Resultsmentioning
confidence: 99%